Design and Analysis of a Parallel Elastic Rod Robot Mechanism for Pick and Place Task - Zhang Junxia Zhang Qiuchen (Jixie chuandong)
In the industrial field，the rigid mechanism design of the pick-and-place robot tends to be mature，but it has the defects of has a lot of mass and high risk factor when human and machine work together. At the same time，as a new design material，the elastic rod has been applied in the fields of medical treatment and exploration due to its own material advantages. Based on this，a parallel elastic rod robot mechanism that can be applied to pick-and-place tasks is proposed. By using the simplified Cosserat elastic rod model，the deformation of the elastic rod is described from the perspective of rigid body motion，and the dynamics model of the elastic rod is derived. The equation and virtual prototype model of the parallel elastic rod are established in Matlab. Through the analysis of key materials and workspace，the corresponding mechanism parameters are obtained. The relationship between the input angle，the torque and the displacement of the end-effector is studied. The feasibility of the theory and the rationality of the design are verified by setting up the prototype，which also provides a reference for the industrial application of the elastic rod.